Effects of Early Life Exposure to Sex Hormones on Neurochemical and Behavioral Responses to Psychostimulants in Adulthood: Implications in Drug Addiction - Renard, G (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Early life exposure to sex hormones affects several brain areas involved in regulating locomotor and motivation behaviors. Our group has shown that neonatal exposure to testosterone propionate (TP) or estradiol valerate (EV) affected the brain dopamine (DA) system in adulthood. Here, we studied the long-lasting effects of neonatal exposure to sex hormones on behavioral and neurochemical responses to amphetamine (AMPH) and methylphenidate (MPD). Our results show that AMPH-induced locomotor activity was higher in female than male control rats. The conditioned place preference (CPP) to AMPH was only observed in EV male rats. In EV female rats, AMPH did not increase locomotor activity, but MPD-induced CPP was observed in control, EV and TP female rats. Using in vivo brain microdialysis, we observed that AMPH-induced extracellular DA levels were lower in nucleus accumbens (NAcc) of EV and TP female rats than control rats. In addition, MPD did not increase NAcc extracellular DA levels in EV rats. Using in vivo fast-scan cyclic voltammetry in striatum, MPD-induced DA reuptake was higher in EV than control rats. In summary, our results show that early life exposure to sex hormones modulates mesolimbic and nigrostriatal DA neurons producing opposite neurochemical effects induced by psychostimulant drugs in NAcc or striatum. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.